2018
DOI: 10.1016/j.qref.2017.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Stock return predictability and model instability: Evidence from mainland China and Hong Kong

Abstract: Highlights  This paper examines the predictability of the Shanghai Composite, Shenzhen Composite and the Hang Seng China Enterprise index returns, with emphasis on whether considering structural breaks in model parameters improves the stock return predictability.  Results are important for investors who are interested in investing in Mainland China and Hong Kong stock markets.  Results indicate higher linear stock return predictability for the Hong Kong market than for the Chinese markets.  Results differ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…Together with the evidence of the BIC and the SM for the number of true breaks, we conclude with one-break prediction models for both S&P 500 and DJIA returns. These findings reinforces those in prior studies that predictive regression models are characterized by structural instability (e.g., Rapach and Wohar 2006 ; Paye and Timmermann 2006 ; Hong et al 2018 ).…”
Section: Covid-19 and Instability Of Stock Return Predictabilitysupporting
confidence: 91%
See 3 more Smart Citations
“…Together with the evidence of the BIC and the SM for the number of true breaks, we conclude with one-break prediction models for both S&P 500 and DJIA returns. These findings reinforces those in prior studies that predictive regression models are characterized by structural instability (e.g., Rapach and Wohar 2006 ; Paye and Timmermann 2006 ; Hong et al 2018 ).…”
Section: Covid-19 and Instability Of Stock Return Predictabilitysupporting
confidence: 91%
“…More recent studies extend the prior research to allow for multiple breaks, unit root dynamics, heteroskedasticity and serial correlation (e.g., Bai and Perron 1997 , 1998 , 2003 ; Elliott and Muller 2004 ; Lee et al 2021 ). Empirical investigation based on those recent econometric techniques includes Paye and Timmermann ( 2006 ), Rapach and Wohar ( 2006 ), and Hong et al ( 2018 ). In this paper, we consider the methodology of Bai and Perron ( 1998 , 2003 ) because it allows us to determine the confidence intervals for the timing of break occurrence as well as the coefficients around the breakpoints.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the results of GARCH models with dummy variables also show that DUM 1 and DUM 2 are significant for the SSEC return in all sets of GARCH models which means that the Asian financial crisis and the global financial crisis influence the stock market return significantly. For China, Hong et al (2018) have also found structural breaks in the Shenzhen stock market and have documented significant improvement in the forecasting of stock market return. For the macroeconomic variables, the impact of global financial crisis is more stern as compared to the Asian financial crisis.…”
Section: Garch Models Analysismentioning
confidence: 99%